Urological Manifestation of Mpox Virus: A Scoping Review - Mantica G; Drocchi G; Chierigo F; Granelli G; Trani G; Paraboschi I; Alba S; Ambrosini F; De Klerk C; Riccardi N; Nozza S; Van der Merwe A; et al. (Research and Reports in Urology, 2025)
Guglielmo Mantica,1 Giovanni Drocchi,1 Francesco Chierigo,2 Giorgia Granelli,1 Giorgia Trani,1 Irene Paraboschi,3 Stefano Alba,4 Francesca Ambrosini,1 Cecelia De Klerk,5 Niccolò Riccardi,6 Silvia Nozza,7 André Van der Merwe,5 Carlo Terrone1 1Department of Surgical and Diagnostic Integrated Sciences (DISC), University of Genoa; IRCCS Ospedale Policlinico San Martino, Genoa, Italy; 2Department of Urology, ASST Santi Paolo e Carlo, Milan, Italy; 3Department of Biomedical and Clinical Sciences, University of Milano, Milan, Italy; 4Romolo Hospital, Rocca di Neto (KR), Rocca di Neto, Italy; 5Division of Urology, Faculty of Medicine and Health Sciences, Stellenbosch University, Cape Town, 7100, South Africa; 6CRR-TB, ASST Grande Ospedale Metropolitano Niguarda, Milan, Italy; 7Infectious Diseases Unit, IRCCS San Raffaele Scientific Institute, Milan, ItalyCorrespondence: Guglielmo Mantica, Email guglielmo.mantica@gmail.comBackground: Mpox primarily presents with systemic and cutaneous symptoms. However, it can also lead to urological complications, necessitating specialized attention. The aim of this scoping review is to summarize the current evidence regarding the urological manifestations of Mpox, possible complications, and available treatments.Methods: An electronic systematic search of the current literature was conducted through the Medline and NCBI PubMed and Scopus databases on 18th August 2024. Our study search and inclusion criteria were in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. 9 The search terms and keywords used were: “monkeypox; Mpox” (MeSH Terms), combined with different terms: “urology”, “kidney”, “ureter”, “bladder”, “prostate”, “genitals”, “penis”, “testicles”, “urethra”, in all different possible combinations.Results: A total of 32 articles included in the scoping review. A total of 116 patients were included, all males. The genitals were the most interested organs, associated with urethritis, while bladder and kidneys seemed to be not impacted by the disease. Patients were usually young, with a mean age of 36 years [31.5– 40 years]. The most prevalent risk factor was sexual intercourse in the days/weeks before the appearance of symptoms. All patients had a molecular confirmatory diagnosis by a polymerase chain reaction (PCR) test. Five articles out of 32 (15.6%) reported the need for surgical debridement of penile and genital lesions due to their clinical worsening. However, in most reports, patients experienced spontaneous resolution of the lesions and symptoms.Conclusion: Awareness of Mpox and timely diagnosis are crucial for ensuring appropriate treatment and reducing the need for surgical management and the possible risk of long-term sequelae. Collaboration among dermatologists, infectious disease specialists, and urologists is pivotal to effectively managing Mpox patients.Keywords: mpox, monkeypox, urology, UTIs, infections